Hexahydrocurcumin alleviated blood–brain barrier dysfunction in cerebral ischemia/reperfusion rats - Piyawadee Wicha (2020)
© 2020, Maj Institute of Pharmacology Polish Academy of Sciences. Background: Hexahydrocurcumin (HHC), a major metabolite of curcumin, has been reported to have protective effects against ischemic and reperfusion damage. The goal of the present research was to examine whether HHC could alleviate brain damage and ameliorate functional outcomes by diminishing the blood–brain barrier (BBB) damage that follows cerebral ischemia/reperfusion. Methods: Middle cerebral artery occlusion was induced for 2 h in rats followed by reperfusion. The rats were divided into three groups: sham-operated, vehicle-treated, and HHC-treated groups. At the onset of reperfusion, the rats were immediately intraperitoneally injected with 40 mg/kg HHC. At 48 h after reperfusion, the rats were evaluated for neurological deficits and TTC staining. At 24 h and 48 h after reperfusion, animals were sacrificed, and their brains were extracted. Results: Treatment with HHC reduced neurological scores, infarct volume, morphological changes, Evans blue leakage and immunoglobulin G extravasation. Moreover, HHC treatment reduced BBB damage and neutrophil infiltration, downregulated myeloperoxidase, ICAM-1, and VCAM-1, upregulated tight junction proteins (TJPs), and reduced aquaporin 4 expression and brain water content. Conclusion: These results revealed that HHC treatment preserved the BBB from cerebral ischemia/reperfusion injury by regulating TJPs, attenuating neutrophil infiltration, and reducing brain edema formation. Graphic abstract: [Figure not available: see fulltext.].